Associations of gallbladder and gallstone parameters with clinical outcomes in patients with cirrhosis - Ding, Min; Yin, Yue; Wang, Xueying; Zhu, Menghua; Xu, Shixue; Wang, Le; Yi, Fangfang; Abby Philips, Cyriac; Gomes Romeiro, Fernando [UNESP]; Qi, Xingshun (De Gruyter, 2023)
Morphologic changes in the gallbladder and gallstones are common in cirrhotic patients, but their associations with outcomes of cirrhotic patients are unclear. We retrospectively enrolled 206 cirrhotic patients and measured their gallbladder length and width, gallbladder wall thickness, presence of gallstones, and gallstones' length and width in axial contrast-enhanced computed tomography (CT) images. X-tile software was utilized to calculate the optimal cutoff values of these parameters for evaluating survival and hepatic decompensation events in the cirrhosis group. Their associations with survival were explored by Cox regression analyses and Kaplan-Meier curve analyses. Their associations with hepatic decompensation events were evaluated by competing risk analyses and Nelson-Aalen cumulative risk curve analyses where death was a competing event. Cirrhotic patients with gallbladder length < 72 mm had a significantly higher cumulative survival rate than those with a length of ≥ 72 mm (P = 0.049 by log-rank test), but gallbladder width, gallbladder wall thickness, presence of gallstones, and gallstones' length and width were not significantly associated with survival (P = 0.10, P = 0.14, P = 0.97, P = 0.73, and P = 0.73 by log-rank tests, respectively). Cirrhotic patients with gallbladder wall thickness < 3.4 mm had a significantly lower cumulative rate of hepatic decompensation events than those with a wall thickness of ≥ 3.4 mm (P = 0.02 by Gray's test), but gallbladder length and width, presence of gallstones, and gallstones' length and width were not significantly associated with hepatic decompensation events (P = 0.15, P = 0.15, P = 0.54, P = 0.76, and P = 0.54 by Gray's tests, respectively). Changes in gallbladder length and gallbladder wall thickness, rather than gallstone parameters, may be in parallel with the long-term outcomes of cirrhotic patients.
Keywords: decompensation; gallbladder; gallstone; liver cirrhosis; survival